2022
DOI: 10.3389/fonc.2022.967100
|View full text |Cite
|
Sign up to set email alerts
|

Colon Sparing Endoscopic Full-Thickness Resection for Advanced Colorectal Lesions: Is It Time for Global Adoption?

Abstract: The majority of colon lesions are <10 mm in size and are easily resected by endoscopists with appropriate basic training. Lesions ≥10 mm in size are difficult to remove technically and are associated with higher rates of incomplete resection. Currently, the main endoscopic approaches include endoscopic mucosal resection (EMR) for lesions without submucosal invasion, and endoscopic submucosal dissection (ESD) for relatively larger lesions involving the superficial submucosal layer. Both of these approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…There were no signi cant adverse events happened. Subsequently, many studies have suggested that nonexposed EFTR is safe and effective in the treatment of colorectal lesions, but the lesions involved in the study are mostly mucosal lesions, and there are only a few reports of submucosal tumors [11,19]. In our study, we demonstrated a total technical success rate of 100% for exposed EFTR on treatment of colorectal SMTs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…There were no signi cant adverse events happened. Subsequently, many studies have suggested that nonexposed EFTR is safe and effective in the treatment of colorectal lesions, but the lesions involved in the study are mostly mucosal lesions, and there are only a few reports of submucosal tumors [11,19]. In our study, we demonstrated a total technical success rate of 100% for exposed EFTR on treatment of colorectal SMTs.…”
Section: Discussionmentioning
confidence: 52%
“…Considering that closed EFTR devices such as FTRD are not available in most of the endoscopy centers in China. And, in recent years, endoscopic suturing devices and technologies such as OTSC system, purse suture with clip and nylon rope have been proved to be effective in suturing of gastrointestinal wall defects [10,11]. In our study, we aimed to research the safety and e cacy of exposed EFTR in the treatment of colorectal SMTs through retrospective data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the non-exposed approach involves pinching off the lesion with a clip or sutures before resecting the lesion with a snare just above the clip or suture line. Common closure devices include endoclips for small (< 1 cm) defects and over-the-scope clips or Overstitch for larger defects [ 34 ]. An over the scope full thickness resection device that employs a clip over a large cap (Ovesco) with an embedded snare fitted on the tip of a colonoscope has been successfully used for resection of fibrotic polyps as well as those growing into a diverticulum or the appendiceal orifice [ 35 ] ( Image 9 ).…”
Section: Large Polyp Removalmentioning
confidence: 99%